Tantangan Menulis Ilmiah Mahasiswa Pendidikan Biologi di Tahun Pertama sebagai Upaya Peningkatan Kepercayaan Diri dan Pencegahan Plagiarisme - Yuswa Istikomayanti; Zuni Mitasari (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
Writing an academic script is not an easy thing even for final semester students at the Tribhuwana Tunggadewi University campus. Through the subjects of Scientific Writing Techniques is given in the second semester (two) as an effort to improve the ability of scientific writing from an early age . This course is given to the students of Biology Education Program, Faculty of Education, Tribhuwana Tunggadewi University, in the first year as an effort to improve the ability to construct ideas into script. This action research has been able to increase students' self-confidence to write using their own language, to develop a background, to be able to cite a reference, to frame a framework of thinking, to write ideas, to write a bibliography, and directly to increase confidence by decreasing frequency of plagiarism. The improvement of aspects in scientific writing is done by several actions: direct instruction, group discussion, peer assessment, and presentation. This action has succeeded in improving the quality of the manuscript measured at the eighth (8th) and 14th (fourteen) meetings, averaging 55 (low categories) to the average 75 (medium category), with the best manuscript 89 (very good).